Analysing green supply chain management practices in Brazil's electrical/electronics industry using interpretive structural modelling - Govindan, Kannan; Kannan, Devika; Mathiyazhagan, K.; de Sousa Jabbour, Ana Beatriz Lopes; Jabbour, Charbel José Chiappetta (Taylor & Francis, 2013)
Industries need to adopt the environmental management concepts in the traditional supply chain management. The green supply chain management (GSCM) is an established concept to ensure environment-friendly activities in industry. This paper identifies the relationship of driving and dependence that exists between GSCM practices with regard to their adoption within Brazilian electrical/electronic industry with the help of interpretive structural modelling (ISM). From the results, we infer that cooperation with customers for eco-design practice is driving other practices, and this practice acts as a vital role among other practices. Commitment to GSCM from senior managers and cooperation with customers for cleaner production occupy the highest level. © 2013 Copyright Taylor and Francis Group, LLC.
Keywords: Green supply chain; Interpretive structural modelling (ISM)